ENGLISH PROFICIENCY IN KELANTANESE ISLAMIC SCHOOLS: AN OVERVIEW OF CHALLENGES, STRENGTHS, AND PEDAGOGICAL IMPLICATIONS - Muhammad, Nur Farhana; Tuan Kechik, Tuan Siti Mastazameatun Long (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study examines the current state of English proficiency within the specialized educational context of Kelantanese Islamic schools in Malaysia. Despite national efforts to align English language education with international standards such as the Common European Framework of Reference (CEFR), significant proficiency gaps persist among learners in religious-based institutions. Guided by the PRISMA 2020 and PCC frameworks, this study synthesized 10 high-quality empirical articles published between 2020 and 2026 to identify the primary factors influencing language outcomes and the efficiency of contemporary pedagogical interventions. The findings reveal that learners consistently demonstrate weaknesses in listening, writing, and foundational literacy, largely attributed to systemic barriers such as a ‘crowded curriculum’ that prioritizes religious studies and a lack of authentic communicative exposure. However, the results also highlight the transformative potential of structured pedagogical scaffolding, specifically genre-based writing, and the strategic integration of Educational Technology (EdTech), including generative AI and cloud-based multimedia tools, to foster learner autonomy and linguistic immersion. The study concludes that improving English proficiency in these institutions requires a multifaceted approach that aligns school-based assessment with national benchmarks while adopting context-sensitive, technology-assisted instruction. These insights provide a critical roadmap for educators and policymakers to enhance the academic mobility and global employability of students within the Islamic educational ecosystem.